2013
DOI: 10.1002/cncr.27941
|View full text |Cite
|
Sign up to set email alerts
|

Agent Orange as a risk factor for high‐grade prostate cancer

Abstract: PURPOSE Agent Orange exposure (AOe) is a potential risk factor for the development of prostate cancer (PCa). However, it is unknown whether AOe specifically increases the risk of lethal PCa. This study aimed to determine the association between AOe and the risk of detecting high-grade PCa (HGPCa, Gleason ≥ 7) on biopsy in a US Veteran cohort. METHODS Risk factors included clinico-demographic and laboratory data from veterans referred for an initial prostate biopsy. Outcomes were defined as the presence versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 10 publications
0
40
0
2
Order By: Relevance
“…Pesticides have been shown to lead to human cancer. For example, the pesticides that have alkyl ureas or amines are connected to brain tumors; dieldrin induces tumorigenesis of the lung, liver, lymphoid tissues, uterus, as well as thyroid; and the risk for prostate cancer is higher in patients exposed to Agent Orange . A prior investigation revealed that a trivalent pesticide‐related chemical can cause protein carbonylation and oxidative DNA damage in human urothelial cells, ultimately resulting in bladder cancer …”
Section: Discussionmentioning
confidence: 99%
“…Pesticides have been shown to lead to human cancer. For example, the pesticides that have alkyl ureas or amines are connected to brain tumors; dieldrin induces tumorigenesis of the lung, liver, lymphoid tissues, uterus, as well as thyroid; and the risk for prostate cancer is higher in patients exposed to Agent Orange . A prior investigation revealed that a trivalent pesticide‐related chemical can cause protein carbonylation and oxidative DNA damage in human urothelial cells, ultimately resulting in bladder cancer …”
Section: Discussionmentioning
confidence: 99%
“…Men exposed to Agent Orange were also diagnosed at a younger age compared to men who were not exposed to the carcinogen. In conclusion, exposure to Agent Orange appears to increase the detection of prostate cancer and incidence of high-grade prostate cancer; however, one must be cautious that these findings are not, at least partially, explained by selection bias [32].…”
Section: Other Considerations (Agent Orange)mentioning
confidence: 88%
“…During this period, the military used large amounts of a defoliant called Agent Orange to eliminate forest cover. In a study conducted at Portland Medical Center and Oregon Health Sciences University, it was found that veterans exposed to Agent Orange were not only more likely to develop prostate cancer, but also more likely to develop a more aggressive form of the disease [32]. Agent Orange exposure is associated with a 52% increase in the detection of prostate cancer and a 75% increased risk of high-grade prostate cancer [32].…”
Section: Other Considerations (Agent Orange)mentioning
confidence: 99%
“…Furthermore, the patients exposed to AO developed PC at a younger age and had more aggressive pathology when compared with their unexposed counterparts [9]. Similarly, Ansbaugh et al [10] demonstrated an increased risk of high-grade PC on biopsy and suggested that AO exposure could be used to intelligently screen patients for PC.…”
Section: Introductionmentioning
confidence: 98%